The Impact of Using Red Clay Bricks on Air Conditioning Efficiency in Buildings Located in Desert Regions: A Case Study of Ghat, Libya - Mustafa Mithali Muhammad Sidi Ali (Journal of Scientific and Human Dimensions, 2026)
Copyright: © 2026 by the authors. This article is an open-access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https://creativecommons.org/licenses/by/4.0/). Abstract: This study aims to evaluate the impact of using red bricks on the efficiency of air conditioning systems in buildings located in desert areas, with a case study in Ghat, Libya. Data were collected through a field survey involving 32 participants from the local population, alongside an analysis of climatic indicators for the summer of 2024. The research focused on the relationship between the type of building material (red bricks) and the cooling performance inside buildings, as well as user perceptions regarding the feasibility of using this material under harsh climatic conditions. The results revealed that a significant proportion of participants observed a relative improvement in the thermal performance of buildings constructed with red bricks, although awareness of the material’s actual impact varied. The data also showed that split air conditioners are the most commonly used in the region and that electricity consumption during summer is generally high, indicating a need for more energy-efficient building solutions. The study concludes that there is a growing societal willingness to adopt traditional and sustainable building materials such as red bricks, provided that sufficient awareness and technical support are available. It recommends integrating such materials into desert building strategies and promoting awareness of their benefits at both individual and institutional levels